An Attempt of Determining the Force Characteristics of Fields in Magnetic Stereotactic System - Аврунін, О. Г.; Elamir Abu Abaida Ali. Osman; Mustafa O. Ali; P. Chandra Sekhar (International Journal of Engineering Science and Innovative Technology (IJESIT), 2012)
Method for analytical determination of the components of magnetic field induction vector and gradient characteristics of magnetic field in stereotactic magnetic neurosurgery systems has been investigated. Components of power vector acting on a surgical instrument from magnetic coil field have been determined and the analysis of topography of magnetic field power characteristics has been carried out.
Keywords: Magnetic Fields; Magnetic Stereotactic System; Magnetic Controlling Surgical Instrument; Contactless Stereotactic